1984
DOI: 10.1093/nar/12.3.1401
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation in SV40 as a mechanism of transcription-termination by RNA polymerase B

Abstract: Nuclei which were isolated from SV40 infected cells with a hypotonic detergent-free buffer were used to establish in vitro conditions which lead to transcription-termination at the attenuation site of SV40. This system allowed us to identify regulatory elements involved in transcription-termination by RNA polymerase B transcribing SV40. Transcription-termination at the attenuation site was found to be ionic strength dependent. Efficient termination occurred at low (100 mM NaCl) but not at high (100 mM (NH4)2 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
35
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 34 publications
2
35
0
Order By: Relevance
“…Furthermore, some Burkitt's lymphoma cell lines that have deregulated c-myc gene expression also have a concentration of mutations in the first exon and intron that correlate with abrogation of the transcriptional block (8). Similar intragenic transcriptional blocks have been observed in the human histone H3.3 gene (46), the human immunoglobulin ,u heavy-chain gene (19,35), the murine c-myc gene (40), the murine c-myb gene (2), the hamster c-fos gene (17), the Drosophila hsp70 gene (21), the simian virus 40 late region (23,24,25,42), the adenovirus major late transcription unit (16,18,33,39,41), and the human immunodeficiency virus type 1 long terminal repeat (31). Modulation of transcription elongation and termination is therefore a general mechanism for the regulation of gene expression in eucaryotic organisms.…”
mentioning
confidence: 63%
“…Furthermore, some Burkitt's lymphoma cell lines that have deregulated c-myc gene expression also have a concentration of mutations in the first exon and intron that correlate with abrogation of the transcriptional block (8). Similar intragenic transcriptional blocks have been observed in the human histone H3.3 gene (46), the human immunoglobulin ,u heavy-chain gene (19,35), the murine c-myc gene (40), the murine c-myb gene (2), the hamster c-fos gene (17), the Drosophila hsp70 gene (21), the simian virus 40 late region (23,24,25,42), the adenovirus major late transcription unit (16,18,33,39,41), and the human immunodeficiency virus type 1 long terminal repeat (31). Modulation of transcription elongation and termination is therefore a general mechanism for the regulation of gene expression in eucaryotic organisms.…”
mentioning
confidence: 63%
“…Interestingly, it has been shown that premature termination during transcription of the mouse 13-major globin gene (33), the c-myc gene (5), and the Drosophila heat shock gene hsp-70 (43) can vary with the physiological state of the cells. Premature termination termed attenuation, has been shown to regulate the quantity of mRNA of several animal viruses, including simian virus 40 (SV40) (1,14,15,48,49), polyomavirus (47), the parvovirus minute virus of mice (2, 40), adenovirus type 2 (Ad2) (23,24,45), and human immunodeficiency virus types 1 and 2 (21, 54). These observations indicate that regulation of gene expression can be exerted at the level of elongation by RNA polymerase II.…”
mentioning
confidence: 99%
“…Premature termination termed attenuation, has been shown to regulate the quantity of mRNA of several animal viruses, including simian virus 40 (SV40) (1,14,15,48,49), polyomavirus (47), the parvovirus minute virus of mice (2,40), adenovirus type 2 (Ad2) (23,24,45), and human immunodeficiency virus types 1 and 2 (21,54). These observations indicate that regulation of gene expression can be exerted at the level of elongation by RNA polymerase II.…”
mentioning
confidence: 99%
“…Therefore, the strong possibility exists that the study of 3'-end formation of an mRNA in yeast cells will shed light on the actual transcription termination event. Termination is known to be important in the regulation of a variety of bacterial operons (reviewed in references 17 and 24) and appears to be involved in the regulation of at least one eucaryotic gene (9,10,28). We have been investigating the sequence determinants of transcription termination on a DNA segment in S. cerev,isiae.…”
mentioning
confidence: 99%